2004
DOI: 10.1111/j.1547-5069.2004.04029.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cultural Sensitivity Training on Health Care Provider Attitudes and Patient Outcomes

Abstract: The results of this study indicate that a cultural sensitivity training program not only improved knowledge and attitudes among health care providers, but it also yielded positive health outcomes for their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 23 publications
(19 reference statements)
7
126
2
3
Order By: Relevance
“…Moreover, our findings illustrate the importance of provider sensitivity and the need for specialized training of health care professionals. This point is supported by others who have written about the importance of provider sensitivity for optimizing HIV treatment [34][35][36].…”
Section: Notes: or = Odds Ratio CI = Confidence Intervalsupporting
confidence: 53%
“…Moreover, our findings illustrate the importance of provider sensitivity and the need for specialized training of health care professionals. This point is supported by others who have written about the importance of provider sensitivity for optimizing HIV treatment [34][35][36].…”
Section: Notes: or = Odds Ratio CI = Confidence Intervalsupporting
confidence: 53%
“…A variety of studies have found a relationship between training and CNA performance (e.g., Majumdar, et al, 2004;Burgio, et al, 2000). Our analyses support these previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…And, in most cases, training was found to have desirable effects. For example, Majumdar, Browne, Roberts and Carpio (2004) randomly assigned 114 nurses and homecare workers to experimental (training) and control groups. After one year, they found that patients who received care from trained providers showed more improvement in functional capacity.…”
Section: Effects Of Training On Cna Performancementioning
confidence: 99%
“…Health policies should therefore be directed towards improving cultural competence training to facilitate partnership working between patients and their healthcare providers. This has been shown to improve professional skills, cultural knowledge and attitudes among healthcare professionals, enabling them to work effectively in cross-cultural situations, thereby yielding positive health-related outcomes for their ethnic minority patients (Majumdar et al, 2004;Khanna et al, 2009).…”
Section: Discussionmentioning
confidence: 99%